Copper-free click bioconjugation of technetium-99m complexes using strained cyclononyne derivatives. Issue 10 (13th February 2023) - Schlesinger, Marlene; Jentschel, Christian; Pietzsch, Hans-Jürgen; Kopka, Klaus; Mamat, Constantin
Abstract : A new, powerful and Cu-free click-labelling method based on the diazacyclononyne (DACN) structure was elaborated using the  99m Tc-tricarbonyl core. Abstract : Click chemistry, in particular copper-free click reactions, has gained growing interest for radiolabelling purposes in the field of radiopharmaceutical sciences. [ 99m Tc][Tc(CO)3 (H2 O)3 ] + works as an excellent starting complex for the radiolabelling of biomolecules under mild conditions. A new chelator, investigated for the copper-free strain-promoted cycloaddition (SPAAC), was synthesised containing the 2, 2′-dipicolylamine (DPA) moiety for the 99m Tc-tricarbonyl core and compared with a DPA chelator based on activated esters for conventional radiolabelling. For the copper-free click labelling procedure, a DPA containing 4, 8-diazacyclononyne moiety was prepared from a sulfonyl-modified diamide (four steps, 64% yield) followed by the Nicholas reaction with butyne-1, 3-diol. The 99m Tc-DPA-DACN-complex was prepared with a radiochemical conversion (RCC) of 89% after 30 min. The following SPAAC reaction with an azide-functionalised PSMA molecule was performed within 4–5 hours at 100 °C to obtain the PSMA (prostate-specific membrane antigen) targeting 99m Tc-complex with 79% RCC and without side products. For comparison, a second DPA-chelator based on a tetrafluorophenyl (TFP) ester was prepared (three steps, 64% yield) and was successfully radiolabelled with [[ 99m Tc]Tc(CO)3 (H2 O)3 ] + with 89% RCC after 20 min and >99% radiochemical purity after separation using an RP18 cartridge. The subsequent conjugation of an amine-functionalised PSMA targeting molecule was performed with 23% RCC after 150 min. Two other unknown side products were observed indicating the decomposition of the TFP ester during the labelling. All nonradioactive Re(CO)3 complexes were synthesised from (Et4 N)2 [ReBr3 (CO)3 ] (91% yield for the nat Re-DPA-TFP ester, 76% yield for nat Re-DPA-DACN) and characterised to confirm the identity of the 99m Tc-complexes.